SINO-NIGERIA RELATIONS AND GLOBAL OIL POLITICS, 1999-2023: ASYMMETRICAL OR SYMMETRICAL? - RUTH O. OGUNNOWO; SAMUEL S. OJO (International Studies Journal)
Nigeria's decreasing foreign investment has heightened Europe's and the USA's interest in investing amid this climate of uncertainty. However, China's quest for resources to ensure its energy security has countered this apprehension. China, the world's most populous nation, requires more imported oil to fuel its rapidly growing economy, while Nigeria, Africa's most populous country, needs infrastructure to accelerate its development. This paper examines Sino-Nigerian relations within the context of global politics, focusing on China's primary interest in securing access to Nigeria's natural resources to sustain its expanding economy. Unlike previous studies that predominantly framed Sino-Nigerian relations through a lens of simple economic exchange, this paper delves deeper into the intricacies of political and socio-economic interactions, highlighting how these factors create an interdependent relationship. It scrutinizes the bilateral agreements, investments, and strategic maneuvers that define the asymmetry or symmetry in this relationship, thereby offering a deeper understanding of how both nations negotiate their positions in the broader context of global oil politics. This approach provides a fresh perspective by combining geopolitical and economic analyses, thus moving beyond the traditional narratives and offering a richer exploration of the subject. This paper employs qualitative method using secondary and internet sources. The findings show that, despite China's positive economic reforms and political stability, which have driven its transformation, Nigeria has not experienced similar benefits. Consequently, the paper argues that, as China, an emerging global power with a booming economy, seeks oil, Nigeria should be recognized as needing significant investment and diversification of its resources.